BENEFICIAL EFFECT OF TAMARINDUS INDICA ON THE LIVER OF ALBINO RAT AFTER FLUORIDE INTOXICATION - P.K. SINGH; KHALIL AHMAD (International Journal of Pharma and Bio Sciences, 2016)
The oxidative stress of fluoride on the liver and beneficial effect of T. indica fruit extract on antioxidant was also studied. The male albino rats of wistar strain were divided into seven groups five in each group. The results of control group was compared with fluoride water injection groups, while T. indica treatment along with fluoride water injection groups were compared with fluoride treated groups. Due to the side effects of ground water fluoride the body weight, organ weight and their ratio decrease significantly, while lipid peroxidation increased significantly and the level of antioxidant like GST, CAT, SOD, and GR were also decreased significantly. But due beneficial effects of T. indica treatment the body weight, organ weight and their ratio increased significantly, while lipid peroxidation decreased significantly and the level of GST, CAT, SOD, and GR were also increased significantly. All result indicate that Tamarindus indica is beneficial as a rich source of antioxidant.